2017
DOI: 10.1016/j.tplants.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Arbuscular Mycorrhizal Fungi: Bread and Butter?

Abstract: Most plants entertain mutualistic interactions known as arbuscular mycorrhiza (AM) with soil fungi (Glomeromycota) which provide them with mineral nutrients in exchange for reduced carbon from the plant. Mycorrhizal roots represent strong carbon sinks in which hexoses are transferred from the plant host to the fungus. However, most of the carbon in AM fungi is stored in the form of lipids. The absence of the type I fatty acid synthase (FAS-I) complex from the AM fungal model species Rhizophagus irregularis sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(108 citation statements)
references
References 90 publications
(75 reference statements)
1
104
0
3
Order By: Relevance
“…We expect to see progress in the description and characterization of plant receptors for AMF signalling molecules as well as in the identification of substrates of receptors and transporters such as D14L/KAI2 and NOPE1 (Gutjahr et al, 2015;Nadal et al, 2017). Physiological and molecular investigation is needed to resolve mechanisms and regulation of nutrient transfer between the symbionts and, in particular, the flux of carbohydrates and lipids towards the fungus (Rich et al, 2017). It is becoming increasingly clear that despite their large host range, the efficiency of AMF in promoting plant performance differs strongly among fungal species and isolates, and the ability of the plant to respond to the symbiosis depends on the plant genotype.…”
Section: Reviewmentioning
confidence: 99%
“…We expect to see progress in the description and characterization of plant receptors for AMF signalling molecules as well as in the identification of substrates of receptors and transporters such as D14L/KAI2 and NOPE1 (Gutjahr et al, 2015;Nadal et al, 2017). Physiological and molecular investigation is needed to resolve mechanisms and regulation of nutrient transfer between the symbionts and, in particular, the flux of carbohydrates and lipids towards the fungus (Rich et al, 2017). It is becoming increasingly clear that despite their large host range, the efficiency of AMF in promoting plant performance differs strongly among fungal species and isolates, and the ability of the plant to respond to the symbiosis depends on the plant genotype.…”
Section: Reviewmentioning
confidence: 99%
“…The development in arbusculated cells of stromulated plastids that can connect to the PM, however, supports a close association of FA-related proteins with the plasmalemma (Fester et al 2001;Ivanov and Harrison 2014;Kumar et al 2014;Pérez-Sancho et al 2016). This development is believed to facilitate the diffusion/uptake of plant FAs by the AM fungus (Rich et al 2017). The mycorrhiza-specific enzyme FatM is localized consistently in stromulated plastids in cells containing arbuscules (Bravo et al 2017).…”
Section: Am-responsive Proteins As Related To Interface Biogenesis Anmentioning
confidence: 99%
“…AM fungi notably assist the plant with the acquisition of mineral nutrients, mainly inorganic phosphate (Pi) and nitrogen (N) that are absorbed from the soil solution by the extra-radical mycelium. In turn, AM fungi are supplied with organic carbon forms essential for them to achieve their full life cycle (Gutjahr and Parniske 2013;Rich et al 2017;Luginbuehl et al 2017). As a result, AM fungi are obligate plant biotrophic microorganisms that have a global impact on plant mineral nutrition and on the carbon cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that fatty acids are transported from the host to the fungus, likely serving as a major nutritive carbon source (Jiang et al ., ; Keymer et al ., ; Luginbuehl et al ., ). However, previously it has been shown that the host also provides sugars as carbon source, although the mechanism by which sugars are transported to the fungus is unclear (Rich et al ., ; Roth & Paszkowski, ; Wang et al ., ). Therefore, in this study we investigated the role of SWEET sugar transporters.…”
Section: Introductionmentioning
confidence: 99%